2020
DOI: 10.3390/app11010045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inter-Repetition Rest vs. Traditional Strength Training on Lower Body Strength, Rate of Force Development, and Muscle Architecture

Abstract: The purpose of the study was to investigate the effect of seven weeks inter-repetition rest vs. traditional strength training on lower body strength, rate of force development (RFD), and vastus lateralis (VL) muscle architecture. Sixteen male participants were assigned into two groups: the inter-repetition rest (IRRG) and the traditional (TG) group. Both groups performed the leg press exercise with four sets of six maximum repetitions (RM) for two training sessions per week. IRRG added a 20 s inter-repetition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
1
10
0
6
Order By: Relevance
“…Specifically, the longer rest allowed resynthesis of phosphocreatine, which is important in execution of explosive actions [28]. The results of this study somehow coincide with previous studies indicating the maintenance of kinetics from longer IRRs [7,8,13,22,23]. For example, Lawton, Cronin [7] demonstrated greater power output (21-25%) during bench press with longer IRR when compared with the continuous set protocols [7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Specifically, the longer rest allowed resynthesis of phosphocreatine, which is important in execution of explosive actions [28]. The results of this study somehow coincide with previous studies indicating the maintenance of kinetics from longer IRRs [7,8,13,22,23]. For example, Lawton, Cronin [7] demonstrated greater power output (21-25%) during bench press with longer IRR when compared with the continuous set protocols [7].…”
Section: Discussionsupporting
confidence: 88%
“…Power, force output and velocity have been demonstrated to decrease with each repetition during high-intensity RT [4][5][6][7][8]. For example, Izquierdo et al [9] posted decreased velocity across repetitions to failure in squat and bench press exercises.…”
mentioning
confidence: 99%
“…Muscle architecture characteristics, namely the muscle thickness, the fascicle angle and the fascicle length ( Figure 3 ), have been considered as important factors contributing to muscle power production [ 66 , 67 , 68 ]. Muscle thickness and fascicle angle have been linked with muscle hypertrophy and strength [ 69 , 70 ]; thus, it is anticipated that athletes with greater muscle mass such as throwers may possess higher muscle thickness and fascicle angles. In addition, athletes with greater muscle thickness and fascicle angle may produce greater muscle strength and power compared to athletes with lower muscle thickness and fascicle angle [ 71 ].…”
Section: Muscle Architecture Characteristicsmentioning
confidence: 99%
“…Although the authors in this study provide interesting data that support the use of cluster sets during the strength-power phase, it is still unknown whether trained athletes can gain the same benefits. In addition, Zaras et al (138) used leg press as their training intervention, which has been reported to be less effective for improving jump performance (134) and maximal strength (85) than free-weight exercises for the lower body, such as the squat. As such, more research on whether other training modalities (e.g., weightlifting movement and their derivatives) using cluster sets elicit greater increases in rapid force-generating capacities and athletic performance in trained individuals is needed.…”
Section: Type Of Set Configuration In the Context Of Training Phasesmentioning
confidence: 99%
“…In summary, traditional sets may be the primary option to be chosen for designing resistance training programs for the hypertrophy phase when considering the scientific literature that reports greater muscle hypertrophy after resistance training using traditional sets (30). However, not all longitudinal studies agree with this argument (5,138). Cluster sets may have the potential to induce greater muscle hypertrophy as they allow for the use of greater training loads.…”
Section: Hypertrophy Phasementioning
confidence: 99%